The Diagnostic Value of Serum L1CAM in Patients With Colorectal Cancer - Ling-Yu Chu MSc; Dong-Ming Guo MSc; Jun-Tian Chen MD; Wang-Kai Fang PhD; Jian-Jun Xie PhD; Yu-Hui Peng MD; Yi-Wei Xu PhD; Xin-Xin Li MD (Technology in Cancer Research & Treatment, 2020)
Objective: Colorectal cancer is one of the most important malignant cancer in the world with high incidence and mortality. Some studies have found that the expression of low serum L1 cell adhesion molecule is associated with poor prognosis in some malignancies. It is suggested that L1 cell adhesion molecule is a candidate serum marker for certain tumors. However, the relationship between serum L1 cell adhesion molecule and colorectal cancer, especially about the diagnostic value, is rarely reported. Therefore, this study aimed to evaluate the diagnostic potential of serum L1 cell adhesion molecule in patients with colorectal cancer. Methods: Enzyme-linked immunosorbent assay was carried out to detect L1 cell adhesion molecule level in sera of 229 patients with colorectal cancer and 145 normal controls. Receiver operating characteristic curves were employed to calculate the accuracy of diagnosis. Results: The levels of serum L1 cell adhesion molecule in the colorectal cancer group were significantly lower than that in normal controls ( P < .05). In the normal group, the area under the receiver operating characteristic curve (area under the curve) of all colorectal cancer was 0.781 (95% confidence interval: 0.734-0.828) and early-stage colorectal cancer was 0.764 (95% confidence interval: 0.705-0.823). With optimized cutoff of 17.760 ng/mL, L1 cell adhesion molecule showed certain diagnostic value with specificity of 90.3% and sensitivities of 43.2% and 36.2% in colorectal cancer and early-stage colorectal cancer, respectively. Clinical data analysis showed that the levels of L1 cell adhesion molecule were significantly correlated with gender ( P < .05) and early and late stages ( P < .05). Furthermore, when compared with carcinoembryonic antigen, serum L1 cell adhesion molecule had significantly improved diagnostic accuracy for both colorectal cancer and early-stage colorectal cancer. Conclusions: Our study demonstrated that serum L1 cell adhesion molecule might be served as a potential biomarker for the diagnosis of colorectal cancer.